Origin and Evolution of Large-Scale Magnetic Fields of Chemically Peculiar Stars. I. Intermediate-Age Clusters - Romanyuk, I. I.; Yakunin, I. A.; Moiseeva, A. V.; Semenko, E. A.; Kudryavtsev, D. O.; Aitov, V. N. (Astrophysical bulletin, 2024)
Chemically peculiar (CP) stars of early spectral types are the only Main-Sequence objects of the Hertzsprung–Russel diagram that have strong magnetic fields covering the entire surface of a star and maintaining a stable structure on a scale of at least decades. The origin and evolution of magnetic fields of CP stars are still a subject of discussion, despite significant progress in the field of observation of stellar magnetic fields and their theoretical description. This situation has developed not least because of the problem of accurately determining the age of CP stars. We performed a review of magnetic fields of CP stars in the Orion OB1 association and five intermediate-age clusters ( Per, Pleiades, NGC 7092, and IC 4756) and found evidence of a strong decrease in the proportion and strength of magnetic fields of CP stars relative to normal stars of the same spectral types. The found dependences can serve as confirmation of the fossil nature of large-scale magnetic fields of stars. The conclusions of this paper are based on the measurements of more than 800 spectra obtained in the period from 2013 to 2023 with the Main Stellar Spectrograph of the 6-m BTA Telescope for about 100 stars.